منهج التحليل الأسلوبي وإشكالية التطبيق - زواري أحمد, علي (جامعة الوادي - University of Eloued, 2017)
ملخص: بحثنا هذا يتحدث عن المنهج التحليلي الأسلوبي وإشكالية التطبيق، الذي تبرز إشكاليته في بيان الإشكالات التي تعترض المحلل الأسلوبي أثناء مقاربته النصوص الأدبية بالمنهج الأسلوبي وما يعتمد عليه من آليات وإجراءات أثناء تطبيقها، وقد حاولنا من خلال ذلك لإبراز أهم النقاط المتعلقة بفك هذا الإشكال، انطلقنا من تقرير المنهج الأسلوبي وأهميته، ثمّ التعريج على علاقة الأسلوبية بالعلوم الأخرى، والاختلاف في بعض المصطلحات في علم الأسلوب، ما أدى إلى اختلاف المنطلقات أثناء التحليل، لنصل بعدها إلى أبرز الإشكالات التي تعترض المحلل الأسلوبي أثناء التطبيق، ونختم البحث بأهم الأسباب الكامنة وراء هذه الإشكالية Abstract: We have discussed in the research paper the stylistic analytical methodology and problematic issue of its application, which highlights the Questions faced by the stylistic analyst during his approach in literary texts to stylistic curriculum and what depends on it as far as the mechanisms and procedures during the application, so, we have tried through it to focus on the most important points In order to clarify that confusion, by establishing stylistic methodology and explaining its importance, then stylistic relationship to other sciences, also, the differences in some of the terminology for the science of style , which led to a different trends during the analysis, and problems faced by stylistic analyst during the application. finally, we have deduced the search by most important underlying causes of this problem..
مقال
Keywords: منهج ؛ التحليل الأسلوبي ؛إشكالية التطبيق